MODERNIZATION OF THE SYSTEM OF PROFESSIONAL TRAINING OF FUTURE PHYSICAL EDUCATION AND SPORTS SPECIALISTS BASED ON INNOVATIVE TECHNOLOGIES - Olimov, Alisher; Эгамбердиев, Рустам (Физическое воспитание, спорт и здоровье, 2023)
MODERNIZATION OF THE SYSTEM OF PROFESSIONAL TRAINING OF FUTURE PHYSICAL EDUCATION AND SPORTS SPECIALISTS BASED ON INNOVATIVE TECHNOLOGIES